Propensão à cooperação: uma análise das empresas de confecções da APL de Cianorte - Rodrigues, Marcelo (2014)
The following research presents the determining attributes of the propensity to cooperate by the companies belonging to the textile cluster (APL – Arranjo Produtivo Local de Vestuário) in Cianorte, PR. Through statistical procedures it was possible to identify two major groups in the referred cluster, with one of the groups less willing to cooperate and the other more prone to cooperation. These groups are uneven in their characteristics even though they are compound in its majority by micro, small and median sized companies. The group with less willingness to cooperate is characterized by the older companies and the other group, which is more willing to cooperate, by the newer companies. It was noticed as well that the number of collaborators do not influence in any way on the willingness to cooperate by the enterprises and, in general, all attest that their participation in the cluster brought benefits to their competitiveness. The cluster is an environment that allows cooperation, even though in some moments the competition prevails, which minimizes the chance to exchange information and also the degree of trust within the network.